Behind The Screen: How Virtual Peer Conformity Affects Cyberbullying Behavior on Indonesian Youth - Nabiel, Furqany Al Haque Qory; Martiarini, Nuke (Journal of Educational, Health and Community Psychology, 2025)
The increasing cases of cyberbullying among adolescents have become a serious issue in various countries, including Indonesia. One of the factors that influences cyberbullying behavior, both perpetrator and victimization, among adolescents is online peer conformity. With the advancement of technology, interactions within online groups enable peer conformity to occur in a virtual context. However, studies examining cyberbullying and peer conformity in the online context are still limited, most of studies focused on non-online conformity, and cyberbullying victimization. This study examined of how peer conformity in virtual groups influences cyberbullying behavior. A cross-sectional survey was conducted among 404 Indonesian adolescents who actively participated in online community or group. The findings revealed a significant positive influence of virtual peer conformity on both cyberbullying perpetration (R² = 0.016, p = 0.011 < 0.05) and victimization (R² = 0.187, p = 0.000 < 0.05). The results can provide empirical grounding for preventive interventions aimed at enhancing adolescents' ability to manage their virtual peer interactions effectively.